Cordial Labeling of the Line Graph of Bistar - BOSMIA, MOHIT; PATEL, MAHENDRA; PARMAR, YAMINI; VIHOL, PRAKASH (Communications in Mathematics and Applications, 2026)
A binary vertex labeling f of a graph G is called a cordial labeling if |vf (0) − vf (1)| ≤ 1 and |ef (0) − ef (1)| ≤ 1. A graph which admits cordial labeling is called a cordial graph. In this paper, the necessary and sufficient conditions for the line graph of Bistar Bn,p to be cordial when p = n + 4m and p = n+4m+2 where m ∈ N ∪ 0 are discussed.